A genetic linkage map in southern‐by‐spring oat identifies multiple quantitative trait loci for adaptation and rust resistance. (10th December 2018) - Sunstrum, Frédérick G.; Bekele, Wubishet A.; Wight, Charlene P.; Yan, Weikai; Chen, Yuanhong; Tinker, Nicholas A.
Abstract: We developed 178 recombinant inbred lines from a southern‐by‐spring oat population designated as "TxH." These lines were genotyped to generate a high‐quality linkage map that resolved 6, 902 markers into 21 linkage groups that matched closely with the latest hexaploid oat consensus map. Three major quantitative trait loci (QTLs) affecting heading date were found in locations that are consistent with known QTLs and candidate genes, and two other QTLs affecting heading date were found in novel locations. Five QTLs affecting plant height were found. Both sets of QTLs are responsible for transgressive segregation observed for these two traits. Four QTLs affecting resistance to crown rust, caused by the pathogen Puccinia coronata f. sp. avenae, were identified. Two of these QTLs are consistent with known clusters of rust resistance genes, while two may represent new locations of novel rust resistance genes. A complete set of SNP sequences suitable for generating markers for molecular selection is provided.